Effects of standardized ileal digestible tryptophan:lysine ratio in diets containing 30% dried distiller grains with solubles on the growth performance and carcass characteristics of finishing pigs in a commercial environment - J A Barnes; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
Two experiments were performed to determine the effects of increasing standardized ileal digestible (SID) tryptophan to lysine (trp:lys) ratio in growing-finishing pig diets containing 30% dried distillers grains with solubles (DDGS). In both experiments, soybean meal replaced crystalline lysine and threonine to alter the dietary SID trp:lys concentrations while maintaining minimum ratios of other amino acids. In Exp. 1, a total of 638 pigs (PIC 1050 x 337, initially 80.0 lb) were used in a 105-d trial with 26 to 27 pigs per pen and 6 pens per treatment. Pens of pigs were randomly allotted to 1 of 4 dietary treatments with standardized ileal digestible trp:lys ratios of 14.0, 15.0, 16.5, and 18.0%. All diets were fed in meal form and treatments were fed in 4 phases. For the overall trial, ADG and ADFI increased (linear; P<0.001) as trp:lys increased through 18%; however, the response tended to be quadratic from d 0 to 42, with optimal ADG and ADFI at 16.5% SID trp:lys. Feed efficiency was not influenced by SID trp:lys ratio. Although feed cost per pig increased (linear; P<0.001) as SID trp:lys ratio increased, so did (linear; P<0.04) final live weight, HCW, income per pig, and income over feed cost (IOFC). The results of this experiment indicated the optimal SID trp:lys ratio was 16.5% from 80 to 160 lb, but at least 18% from 160 to 265 lb. In Exp. 2, a total of 1,214 pigs (PIC 1050 x 337, initially 146.2 lb) were used in a 73-d finishing trial with 25 to 28 pigs per pen and 9 pens per treatment. Pens of pigs were randomly allotted to 1 of 5 treatment groups. Pigs were fed common diets before the start of the experiment. Dietary treatments included corn-soybean meal-based diets with SID trp:lys ratios of 15.0, 16.5, 18.0, and 19.5, and the 15.0% diet with L-tryptophan added to achieve 18.0% SID trp:lys ratio. Overall (d 0 to 73), ADG, ADFI, F/G, final weight, and HCW improved (linear; P<0.03) as dietary SID trp:lys increased through 19.5%. Increasing SID trp:lys increased (linear; P<0.001) feed cost per pig, but also increased (P<0.01) total income per pig. While there were no differences on an IOFC basis, pigs fed the highest level of SID trp:lys had numerically the greatest IOFC. Overall, there were no significant differences between the diet with 18.0% SID trp:lys and the diet with 15.0% SID trp:lys with added L-tryptophan to 18.0%. These experiments demonstrate there is opportunity to improve growth performance in late-finishing pigs with increased SID trp:lys ratios in diets containing high amounts of DDGS.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Amino acid ratio; Dried distillers grains with solubles; Lysine; Tryptophan